Economic Methods of Land Use In Agriculture (Eurasian Research Bulletin, 2024)
This article discusses the problems of protecting agricultural lands in the Republic of Uzbekistan. During the study, issues of improving the existing unified land tax system were considered and, on their basis, proposals and recommendations were made.